COVID-19: epidemiological data of 1263 patients from southern Minas Gerais, Brazil - Romero, Ray B.; Pelizzaro, Rafaela A.; da Silva Filho, Thyago H. N.; Vilela, Ellyson G. de Oliveira; de Oliveira, Camila P.; Rabelo, Ana T. S.; de Assis, Gabriela A.; Mundim, Fiorita G. L.; Amaral, Pedro I. S.; Silvério, Alessandra C. P. (International Journal Of Community Medicine And Public Health, 2022)
Background: COVID-19 is an easily contagious and high-speed viral disease that is directly affecting people's lives and exposing the fragility of health systems around the world, especially in Brazil. In this context, the present research sought to observe, through medical records, the conduct of positive patients with COVID-19. Methods: The methodology used was the analysis of medical records of patients with COVID-19 in five hospitals in Minas Gerais. The following data were collected from patients who were hospitalized from March 2020 to October 2020: personal characteristics; pathological antecedents and evolution of the clinical picture. Results: The results found describe the number of patients in each of the analysed hospitals. In addition, the predominant age, the sex of the patients in percentage, the number of patients with subarachnoid hemorrhage (SAH), chronic obstructive pulmonary disease (COPD), diabetes, dyslipidemia, altered D-dimer, anemia and hematologic change are described. Intensive care unit (ICU) and ward admissions are also addressed, as well as the type of respiratory complication, percentage of individuals who required intubation, intubation time and outcome. The results were used in statistical analysis for the association between variables with the Chi-square test to verify the significance between them. The outcome was compared with age, sex, diabetes, dyslipidemia, D-dimer biomarker, anemia, hematological changes and type of hospitalization. With the type of hospitalization, diabetes and dyslipidemia were compared. Conclusions: Faced with all this context of public health urgency, this work helps in the standardization of variables to collaborate in the fight against this giant and persistent virus that public health is trying to fight.